What I Mean Before This: artistic action with theater audiences - Desgranges, Flávio (Revista Brasileira de Estudos da Presença, 2022)
ABSTRACT - What I Mean Before This: artistic action with theater audiences - The article deals with artistic creation processes carried out with the public through theatrical performances, aiming to highlight elements that constitute an audience poetics. The public is invited to lean over the scene they have watched taking into consideration the impact caused by the work of art. What is sought, from the artistic creation proposed to the audience, is the possibility of language invention, of elaboration of statements that escape the repetitive role models.